Synergistic Effect of Linezolid Incorporated Chitosan Nanoparticles in Restorative Dental Cements – A Promising Dental Formulation.: Life Sciences-Dental - Burhanuddin Mohammed, Omar Farooq; Lakshmipathy, Muthukrishnan; Mohan Kumar, N. Somasundaram; Nivedhitha, M.S. (International Journal of Life Science and Pharma Research, 2023)
Chitosan is considered one of the best materials for use as a drug delivery vehicle. Chitosan is incorporated into dental cement to enhance its properties. Previous investigators have found its antibacterial activity near dental restorations, which was insufficient to produce a clinically significant effect. Hence, the incorporation of various antibacterial agents was proposed. Linezolid is one of the oldest drugs in the oxazolidinone antibiotics category, approved by the US FDA in 2000. It is used to treat various antibiotic-resistant bacterial infections. However, there needs to be more literature regarding using linezolid with chitosan. Current research aims to prepare and characterize chitosan nanoparticles with linezolid for use in dental cement. Chitosan nanoparticles were prepared using the ionotropic gelation technique. They were incorporated with Linezolid, and samples were analyzedby FTIR spectroscopy, Particle size analysis, Transmission Electron Microscopy, High-performance liquid chromatography analysis, antibacterial activity, and biocompatibility. Linezolid was successfully incorporated into chitosan. Chitosan's FTIR spectrum reflected the functional groups present in chitosan, and their peaks were superimposed in the presence of linezolid. Both chitosan and chitosan with linezolid had similar particlesizes (142nm). Linezolid was released from chitosan effectively on the 1st and 7th days (19.78 and 144.14μg/ml). The formulation showed antibacterial activity and was not cytotoxic to cells. Thus prepared linezolid incorporated chitosan is a promising material to be used as an antimicrobial agent in dental cement. Its bio-physico-chemical properties are promising for use in dental cement. In the future, these linezolid-loaded chitosan nanoparticles may be added to various restorative materials.